Dialogue between programmed cell death and psoriasis - Tian, Jun; Zhang, Lei; Yang, Li (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
Psoriasis is a chronic inflammatory skin condition, associated with both physical and psychological burden. The aetiology of psoriasis is not fully understood. Physiologically programmed cell death (PCD) pathways are crucial for maintaining organismal homeostasis. Several investigations have highlighted the link between dysregulated PCD and the initiation of psoriasis. This review aims to outline various forms of programmed cell death pathways, encompassing the psoriasis distinctive features, triggers, implications in psoriasis pathogenesis, and therapeutic opportunities. It aspires to offer a comprehensive exploration of the role of programmed cell death in the context of psoriasis, providing a rational framework for further investigation and potential therapeutic interventions.